The Effects of National Mental Health Plans on Mental Health Services Development in Chile: Retrospective Interrupted Time Series Analyses of National Databases Between 1990 and 2017 - Martinez-Diaz, P (BioMed Central Ltd, 2022)
Aims: To describe changes in mental health services in Chile between 1990 and 2017, and to retrospectively assess the effects of national mental health plans (NMHPs) on mental health services development during this period. Methods: Service data (beds in psychiatric hospitals, psychiatric beds in general hospitals, forensic psychiatric beds, beds in protected housing facilities, psychiatric day hospital places, and outpatient mental health care centers) were retrieved from government sources in Chile. Data were reported as rates per 100,000 population. We conducted interrupted time series analyses, using ordinary least-square regressions with Newey-West standard errors, to assess the effects of the 1993 and 2000 NMPHs on mental health services development. Results: Rates of short- and long-stay beds in psychiatric hospitals (per 100,000 population) were reduced from 4.3 to 3.2 and from 19.0 to 2.0 over the entire time span, respectively. The strongest reduction of short- and long-stay beds in psychiatric hospitals was seen between the 1993 and 2000 NMHPs (annual removal of − 0.14 and − 1.03, respectively). We observed increased rates of psychiatric beds in general hospitals from 1.8 to 4.0, beds in protected housing facilities from 0.4 to 10.2, psychiatric day hospital places from 0.4 to 5.0, outpatient mental health care centers from 0.1 to 0.8 and forensic psychiatric beds from 0.3 to 1.1 over the entire time span. The strongest annual increase of rates of psychiatric beds in general hospitals (0.09), beds in protected housing facilities (0.50), psychiatric day hospital places (0.16) and outpatient mental health care centers (0.04) were observed after the 2000 NMHP. Forensic psychiatric beds increased in the year 2007 (0.58) due to the opening of a new facility. Conclusions: The majority of acute care psychiatric beds in Chile now are based in general hospitals. The strong removal of short- and long-stay beds from psychiatric hospitals after the 1993 NMHP preceded substantial expansion of more modern mental health services in general hospitals and in the community. Only after the 2000 NMHP, the implementation of new mental health services gained momentum. Reiterative policies are needed to readjust mental health services development. © 2022, The Author(s).